Increasing The Performance Of Civil Servants at the Main Secretariat Of The State Service Agency - Bahtiar Al Fikri; Hari Muharam; Ismuhadjar Ismuhadjar (International Journal of Economics and Management Sciences, 2024)
This study aims to identify the influence of organizational culture, transformational leadership, and work motivation on the performance improvement of civil servants at the Main Secretariat of the National Civil Service Agency. Data analysis was conducted using Linear Structural Relationship (Lisrel) version 8.80 with Structural Equation Modeling (SEM) method. The choice of using SEM in this research lies in its ability to analyze the pattern of relationships between latent constructs and their indicators, latent constructs with each other, and measurement errors directly. The results of the analysis indicate that organizational culture, transformational leadership, and work motivation significantly contribute to the improvement of civil servants' performance. Managerial implications and recommendations for further research are also discussed.